"Your Faith Has Made You Well": The Role of Storytelling in the Experience of Miraculous Healing - Singleton, Andrew (Review of religious research, 2001)
Instances of "successful" miraculous physical healing are now commonplace in contemporary Pentecostal and charismatic Christian churches throughout the world. Previous empirical studies of this phenomenon have overlooked the role the social practice of storytelling plays in relation to these experiences. Analyzing a number of oral stories which describe instances of miraculous healing, this study examines how the act of telling a story enables informants to interpret their experiences as a "miracle." This preferred interpretation of events is produced through the ways the informants fashion their stories to privilege particular cultural meanings and suppress others and through the depiction of characters who appear in a miraculous healing story. The study concludes with an analysis of how the widespread circulation of miraculous healing stories sustains the practice of praying for miraculous healing whilst also creating reality for a community.